Assessing the oral health of school-age children and the current school-based dental screening programme in Freiburg (Germany) - D Sagheri (Journal compilation 2007 Blackwell Munksgaard, 2007)
Germany has a three-tiered system of education at secondary school level, divided into the school types ‘Hauptschule’, Realschule’ and ‘Gymnasium’. All students receive, when aged 6–12 years, a uniform annual dental examination and oral health education programme.